INSURANCE-MARKETS EQUILIBRIUM WITH A NON-CONVEX LABOR SUPPLY DECISION, UNOBSERVABLE EFFORT, AND EFFICIENCY WAGES OF THE “NO-SHIRKING” TYPE - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields, 2019)
The purpose of this paper is to describe the lottery and insurance-market equilibrium in an economy with non-convex labor supply decision, unobservable effort, and efficiency wages of the no-shirking type a la Shapiro and Stiglitz (1984). The presence of indivisible labor creates a market incompleteness, which requires that an insurance market for (un) employment be put in operation to "complete" the market.